2005
DOI: 10.1128/jvi.79.10.6432-6440.2005
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus Type 1 Stimulates the Expression and Production of Secretory Leukocyte Protease Inhibitor (SLPI) in Oral Epithelial Cells: a Role for SLPI in Innate Mucosal Immunity

Abstract: The innate immune response is a key barrier against pathogenic microorganisms such as human immunodeficiency virus type 1 (HIV-1). Because HIV-1 is rarely transmitted orally, we hypothesized that oral epithelial cells participate in the innate immune defense against this virus. We further hypothesized that secretory leukocyte protease inhibitor (SLPI), a 12-kDa mucosal antiviral protein, is a component of the host immune response to this virus. Here we demonstrated constitutive expression and production of SLP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
49
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 60 publications
1
49
0
3
Order By: Relevance
“…To examine whether the loss of SLPI was specific for HSV, CaSki cells were also infected with VSV or exposed to 50 ng Previous studies have demonstrated that exposure of human oral epithelial cells or keratinocytes to HIV-1 BaL resulted in an increase in SLPI production, although the effects on genital tract epithelial cells were not examined (24). As an additional control, the cells were treated with the Toll-like receptor 3 (TLR3) agonist poly(I:C), which has been shown to augment SLPI production in the genital tract (1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To examine whether the loss of SLPI was specific for HSV, CaSki cells were also infected with VSV or exposed to 50 ng Previous studies have demonstrated that exposure of human oral epithelial cells or keratinocytes to HIV-1 BaL resulted in an increase in SLPI production, although the effects on genital tract epithelial cells were not examined (24). As an additional control, the cells were treated with the Toll-like receptor 3 (TLR3) agonist poly(I:C), which has been shown to augment SLPI production in the genital tract (1).…”
Section: Resultsmentioning
confidence: 99%
“…J. VIROL. may contribute to the poor oral transmission of HIV (24). Possibly, the more modest increase in SLPI following exposure of cervical epithelial cells to HIV-1 contributes to the increased risk of genital versus oral mucosal transmission.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…WAPs are mostly secreted factors in mucosal tissue with pleiotropic functions implicated in innate immunity; some are serine protease inhibitors with anti-infective activity (20,27). One WAP, secretory lymphocyte protease inhibitor (SLPI), detected in macrophages but not CD4 T cells, exhibits anti-HIV activity by binding to the phospholipid binding protein annexin II, which is a cofactor for macrophage HIV infection (33,35) and is associated with reduced HIV transmission (22,28). ps20, a secreted WAP of approximately 23 kDa with a characteristic N-terminal signal peptide that targets it for extracellular secretion, is reported to modulate cell proliferation, migration, and the formation of multicellular spheroids (31,32,40) and to induce angiogenesis in cancer-associated reactive stroma in vivo (34).…”
mentioning
confidence: 99%
“…6 It was previously shown that HIV-1 stimulates production of SLPI in oral epithelial cells by interacting with the viral glycoprotein gp120, impairing the establishment of infection. 7 In addition, McNeely et al showed that recombinant SLPI or SLPI derived from saliva protected human monocyte-derived macrophages and CD4…”
Section: Introductionmentioning
confidence: 99%